2013
DOI: 10.5714/cl.2013.14.2.089
|View full text |Cite
|
Sign up to set email alerts
|

Size sorting of chemically modified graphene nanoplatelets

Abstract: Size-sorted graphene nanoplatelets are highly desired for fundamental research and technological applications of graphene. Here we show a facile approach for fabricating size-sorted graphene oxide (GO) nanoplatelets by a simple centrifugal method using different dispersion solvents. We found that the small-sized GO nanoplatelets were more effectively separated when dispersed in water or dimethylformamide (DMF) than in an alkali aqueous solution. After several iterations of the centrifugation, the sizes of GO i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…The morphology of chitosan/starch-based nanocomposites containing graphene oxide (GO) is shown in Figure 5 and Figure 6 . The TEM and SEM images show well-distinguished GO plate particles in the polysaccharide composite, which means that the graphene oxide has been successfully assembled into polymers [ 39 , 40 ]. The presence of regularly spaced black sheets indicates that GO has been uniformly dispersed throughout the nanocomposite film and that GO does not aggregate in the polysaccharide matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The morphology of chitosan/starch-based nanocomposites containing graphene oxide (GO) is shown in Figure 5 and Figure 6 . The TEM and SEM images show well-distinguished GO plate particles in the polysaccharide composite, which means that the graphene oxide has been successfully assembled into polymers [ 39 , 40 ]. The presence of regularly spaced black sheets indicates that GO has been uniformly dispersed throughout the nanocomposite film and that GO does not aggregate in the polysaccharide matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The result implies that some marginal increase in the interfacial strength between the carbon fiber and the phenolic matrix may be attainable. It is suggested that incorporating chemically functionalized graphite or graphene nanoplatelets [21] into the carbon fiber surfaces may be beneficial for forming additional interfacial bonding between the fibers and the matrix in the composite, and also for improving the mechanical properties of the resulting carbon fiber/phenolic matrix composite.…”
Section: Characterizationmentioning
confidence: 99%
“…For example, Hersam et al [22][23][24][25] have reported that isopycnic density gradient ultracentrifugation (iDGU) method can precisely control the thickness (layer number) of 2D materials, while their lateral sizes are still broad. On the other hand, Coleman et al reported the sedimentation rate based DGU (sDGU) [2,26] and liquid cascade centrifugation (LCC) [15,[27][28][29] method for lateral size sorting of 2D materials. For the sDGU and LCC sorted 2D materials, their lateral size and thickness are usually correlated.…”
Section: Introductionmentioning
confidence: 99%